Superior treatment efficacy of neuromodulation rehabilitation for upper limb recovery after stroke: a meta-analysis. (3rd October 2022) - Zhi, Jian-Feng; Liao, Qing-Hong; He, Yu-Bo; Xu, Wen-Wen; Zhu, Dan-Wei; Shao, Lin-Hong
ABSTRACT: Background: This study aims to explore the treatment efficacy of different motor rehabilitation interventions for upper limb impairment recovery. Research Design & Methods: Publications were searched in PubMed and Embase. 4 grouped motor rehabilitation treatments (training, technological intervention, pharmacological intervention, and neuromodulation) were compared. The change of the Fugl-Meyer Assessment Scale for Upper Extremity (FMA-UE) was applied to assess upper limb function after stroke. Results: 56 studies including 5292 patients were identified. A significant difference was found among the 4 groups (P = 0.02). Neuromodulation interventions had the best treatment efficacy among the 4 types of interventions (P < 0.01). Among neuromodulation interventions, acupuncture, electric, or magnetic intervention all had therapeutic efficacy for stroke upper limb recovery, without significant subgroup difference (P = 0.34). Stroke patients with mild upper limb impairment might not benefit from motor rehabilitation (P = 0.14). Conclusion: Neuromodulation interventions might have the best therapeutic efficacy among motor rehabilitation treatments for upper limb impairment after stroke. It is a potential treatment direction for upper limb recovery among stroke patients. However, since a large proportion of the original studies are low to very low-quality evidence, large-scale RCTs should be conducted in the future to validate current findings and assess treatment effects based on patient characteristics.